Navigating Parental Knowledge, Experiences, and Challenges Regarding Post-Discharge Care of Preterm Infants - Hayat, Sikandar; Mughal, Beenish Bashir; Shaukat, Ayesha; Kamal, Aaima; Saeed, Farrukh; Butt, Tayyaba Khawar (Biological and Clinical Sciences Research Journal, 2025)
Preterm birth remains a leading cause of neonatal morbidity and mortality globally, with heightened vulnerability persisting after hospital discharge. In resource-limited settings like Pakistan, the caregiving burden shifts predominantly to families, often without adequate preparation or support, leading to adverse outcomes despite advancements in neonatal care. Objective: To explore the knowledge, caregiving experiences, and challenges faced by caregivers of preterm infants after discharge from a tertiary care hospital in Pakistan. Methods: This descriptive, cross-sectional study was conducted in the Neonatology Department of Services Hospital, Lahore, from Nov 2024 to May 2025, following ethical approval (IRB/2025/1530/SIMS). Thirty-six caregivers of preterm infants (born <37 weeks gestation) discharged within the previous six months were recruited through non-probability convenience sampling. Data were collected through structured interviews during follow-up visits using a comprehensive questionnaire covering demographics, infant characteristics, feeding practices, kangaroo mother care practices, hygiene and temperature control, recognition of danger signs, developmental monitoring, emotional well-being, cultural influences, and access to support systems. Descriptive statistics and thematic analysis were used for data interpretation. Results: Most caregivers were mothers (66.7%) with a mean age of 29.94±7.22 years and 44.5% having tertiary level education. Mean infant gestational age was 31.00±2.39 weeks with birth weight 1631.67±429.68g. Primary neonatal diagnoses included respiratory distress syndrome (30.5%), jaundice (22.2%), and sepsis (19.5%). While 83.3% of caregivers knew breastfeeding benefits, only 50% practiced exclusive breastfeeding, with 13.9% incorrectly diluting formula. Hunger cues were confidently recognized by 50% of caregivers. KMC was practiced at home by 44.4% with a mean frequency of 5.1±2.9 hours daily. Despite 83.3% receiving hygiene counseling, only 58.3% consistently practiced good hygiene. Danger sign recognition was limited, with only 27.8% identifying cyanosis, though all caregivers (100%) would seek hospital care when needed. Health concerns were reported in 72.2% of infants, primarily breathing difficulties (27.8%). Developmental concerns were noted by 30.6% of caregivers, while 38.9% reported infants achieving smiling milestones. Follow-up adherence was good (75% attending regular visits), but barriers included scheduling challenges (33.3%), transport issues (11.1%), and financial constraints (5.6%). Traditional practices were used by 47.2% of families. Emotional strain affected 55.5% of caregivers, with stress and fatigue reported by 35.5%. Post-discharge counseling was considered adequate by only 61.1%, while 38.9% received incomplete support. Conclusion: Caregivers of preterm infants face multifaceted challenges after discharge, including significant gaps between knowledge and practice implementation, particularly in exclusive breastfeeding, KMC continuation, and danger sign recognition. Despite relatively high educational levels, practical application of essential neonatal care practices remained suboptimal. Key challenges included feeding difficulties (58.4%), health-related concerns (72.2%), emotional strain (55.5%), and cultural conflicts with medical advice (47.2%). The study reveals urgent needs for structured, culturally-sensitive discharge education extending beyond hospitalization, enhanced psychosocial support addressing maternal mental health, community-based reinforcement mechanisms, and innovative follow-up strategies bridging hospital-to-home care transitions. These findings provide valuable insights for developing targeted interventions to improve neonatal outcomes in similar resource-limited settings.